THE ROLE OF PHYSICO-MORPHIC AND CHEMICAL PLANT CHARACTERS OF DIFFERENT GENOTYPES OF BT-COTTON (GOSSYPIUM HIRSUTUM L.) IN THE POPULATION FLUCTUATION OF JASSID (AMRASCA BIGUTTULA BIGUTTULA) (ISHIDA) (HOMOPTERA: CICADELLIDAE) IN PUNJAB PAKISTAN - J. A. Bhatti; A. Suhail; M. A. Khan; N. Javed (Journal of Animal and Plant Sciences, 2015)
Cotton is one of mostly attacked crop by sucking insect pests, out of which Jassid Amrasca biguttula biguttula (Ishida) (Homoptera: Cicadellidae) has become one of the serious pest of this crop. The present study was conducted on different selected genotypes of the Bt-cotton to find out the role of the physico-morphic and chemical plant characters on the population fluctuation of jassid. The effects of physico-morphic and chemical plant characters of Bt-cotton were correlated with the jassid population and their role was calculated by processing the data into simple and multiple linear regression equation. The maximum variations were observed among the resistance and susceptible genotypes of Bt-cotton due to plant height, hair density, thickness of leaf lamina, leaf area, length of hair, moisture percentage and total minerals. The results revealed that hair density on midrib, vein and lamina had negative and significant correlation, length of hair on midrib and vein had non significant correlation while Thickness of leaf lamina exerted positive and significant correlation with the Jassid population per leaf. Gossypol glands on midrib and vein showed positive and significant correlation while on lamina had negative and significant effect. Total minerals exerted positive and significant effect whereas reducing sugar, calcium and manganese showed negative and significant correlation with the Jassid density. Multiple linear regression models revealed that hair density on midrib and total minerals in the leaves were the most important characters.
Keywords: Bt-cotton; Genotypes; Resistance; Jassid; Physico-Morphic; Chemical characters